The Review of Innovation and Business Performance - Al-Shorman, Mohammad; Alqudah, Tamer Hussein Ahmad; Al qatawneh, Diaa Khalaf Ahmed; Alzoughool, Sameer A A (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this study to review a number of studies on innovation and business performance the several empirical studies reviewed show mixed results and conclusions. In some studies, strong positive relationships are found to exist between innovation and business performance and in some, the relationship is a little weak other scholars report different results. This mixture of findings and conclusions comes from the differences in methodologies, variables used and the period of study. There is also a difference in the study area that effects on business performance and innovation.